2003
DOI: 10.1016/s0378-1097(03)00653-0
|View full text |Cite
|
Sign up to set email alerts
|

Cystine uptake prevents production of hydrogen peroxide byLactobacillus fermentumBR11

Abstract: BspA is an abundant surface protein from Lactobacillus fermentum BR11, and is required for normal cystine uptake. In previous studies, a mutant strain deficient in BspA (L. fermentum PNG201) was found to be sensitive to oxidative stress. In this study, the biochemical basis for this was explored. It was found that under aerobic batch culture conditions in de Mann^Rogosa^Sharpe medium, both L. fermentum BR11 and PNG201 entered stationary phase due to hydrogen peroxide accumulation. However, this took place at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…3, A and B). The latter finding is consistent with the previous observation in L. fermentum (30). It should be noted that, as FliY is a periplasmic solute-binding protein, FliY probably cooperates with a certain transporter for the uptake of L-cystine (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…3, A and B). The latter finding is consistent with the previous observation in L. fermentum (30). It should be noted that, as FliY is a periplasmic solute-binding protein, FliY probably cooperates with a certain transporter for the uptake of L-cystine (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The uptake system of L. reuteri BR11 comprises a high affinity cystine binding protein termed Cystine Uptake C (CyuC), a component of the ATP binding cassette cystine transport system [20]. In order to determine the role of this unique system, the cyuC gene was inactivated using homologous recombination to produce a L. reuteri mutant (PNG201) deficient in cystine uptake [13,21]. Utilizing a rat model of colitis induced by ingesting dextran sulfate sodium (DSS) it was hypothesized that elimination of the CyuC protein, which effectively inactivates the entire transport of cystine, would result in a decreased ability of the bacteria to prevent colonic injury.…”
Section: Lactobacillus Reuteri Br11 (Br11) Is a Bacterial Strain ((Fomentioning
confidence: 99%
“…L. reuteri rapidly transports cystine and converts it to a thiol(s), which is, at least in part, secreted from the cell in a process requiring CyuC (47). A cyuC-deficient mutant was found to be more sensitive to oxidative stress due to overproduction of hydrogen peroxide in the presence of oxygen (18). It was therefore concluded that the CyuC transporter plays a role in oxidative defense of L. reuteri BR11 by deriving thiols from exogenous cystine.…”
mentioning
confidence: 97%
“…In addition, sulfur amino acid lyases are unique in that they are able to produce free thiols without consuming reducing equivalents (47). Therefore, it is reasonable to hypothesize that Cgl works in concert with the CyuC transporter in oxidative defense by cleaving cystine into thiols that act as reductants for thiol peroxidases (18,47). Alternatively, thiols may reduce hydrogen peroxide nonenzymatically, as shown in the spontaneous reaction between sulfides and hydrogen peroxide (42).…”
mentioning
confidence: 99%